2016
DOI: 10.1146/annurev-genet-120215-035227
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the Cycles of Life

Abstract: The life cycles of eukaryotes alternate between haploid and diploid phases, which are initiated by meiosis and gamete fusion, respectively. In both ascomycete and basidiomycete fungi and chlorophyte algae, the haploid-to-diploid transition is regulated by a pair of paralogous homeodomain protein encoding genes. That a common genetic program controls the haploid-to-diploid transition in phylogenetically disparate eukaryotic lineages suggests this may be the ancestral function for homeodomain proteins. Multicell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 122 publications
3
86
1
Order By: Relevance
“…Rather, striking conservation of KNOX/BELL functions in the promotion of karyogamy across phylogenetically distant M. polymorpha and C. reinhardtii suggests that functions of KNOX/BELL heterodimers shifted from zygote-activation to sporophyte development as land plant evolved. This view is consistent with a proposed evolutionary scenario of HD proteins in a broader eukaryotic taxa, including fungi and metazoans (Bowman et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Rather, striking conservation of KNOX/BELL functions in the promotion of karyogamy across phylogenetically distant M. polymorpha and C. reinhardtii suggests that functions of KNOX/BELL heterodimers shifted from zygote-activation to sporophyte development as land plant evolved. This view is consistent with a proposed evolutionary scenario of HD proteins in a broader eukaryotic taxa, including fungi and metazoans (Bowman et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Outside the plant kingdom, TALE TFs in yeasts and fungi promote the haploid-to-diploid transition (Goutte and Johnson, 1988, Herskowitz, 1989, Kües et al, 1992, Spit et al, 1998). Thus, perhaps the shared zygote-activating functions of KNOX/BELL in M. polymorpha and C. reinhardtii reflect an ancestral state (Bowman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of complex, multicellular organisms, it would not have been surprising if additional processes such as developmental networks had come under the control of these regulators as this would have ensured that those developmental processes were deployed at the appropriate stage of the life cycle . Indeed, it has been suggested that modifications to homeodomain-based regulatory circuits may have played an important role in the emergence of sporophyte complexity in the green lineage (Bowman et al, 2016;Lee et al, 2008). Key events may have included the replacement of the Gsp1-like class of BELL-related1 genes with alternative (true BEL-class) proteins and diversification of both the true BELL-class and the KNOX-class TALE HD TFs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the extensive literature on the functions of KNOX/BELL in angiosperms, the only potential known vestige of this ancestral system existing in angiosperms is the presence of KNOX2 function in the Arabidopsis female gametophyte, possibly in the egg cell (Pagnussat et al, 2007). Thus, it seems that the ancestral function has been entirely lost in some derived land plants, as it has presumably in the metazoan lineage (Bowman et al, 2016b). (Marchant, 1713, Mirbel, 1835, Thuret, 1851, Unger, 1837.…”
Section: An Ancestral Function For Tale-hd Genes In the Viridiplantaementioning
confidence: 99%
“…Expression of paralogous homeodomain genes in the two gametes directs the haploid-to-diploid transition in gene expression in phylogenetically diverse eukaryotes, including the ascomycete fungus Saccharomyces cerevisiae (Goutte andJohnson, 1988, Herskowitz, 1989), the basidiomycete fungi Coprinopsis cinerea and Ustilago maydis (Gillissen et al, 1992, Hull et al, 2005, Kues et al, 1992, Spit et al, 1998, Urban et al, 1996, the Amoebozoa Dictyostelium discoideum (Hedgethorne et al, 2017), the brown alga Ectocarpus (Arun et al, 2019), the red alga Pyropia yezoensis (Mikami et al, 2019), and the unicellular Chlorophyte alga Chlamydomonas reinhardtii (Ferris and Goodenough, 1987, Lee et al, 2008, Nishimura et al, 2012, Zhao et al, 2001. This broad phylogenetic distribution suggest this was an ancestral function of homeodomain genes [reviewed in (Bowman et al, 2016b)]. In the Viridiplantae the paralogous genes are two subclasses, KNOX and BELL, of TALE-class homeodomain (HD) genes.…”
Section: Main Text: Introductionmentioning
confidence: 99%